مخاطر السيولة وأثرها على ربحية المصارف التجارية الليبية - الفرجاني د. إبراهيم مسعود; الدرسي أ.عبدالله جادالمولى (Aljameai)
الملخص: هدف البحث إلى قياس مخاطر السيولة والربحية، والتعرف على طبيعة العلاقة بين مخاطر السيولة والربحية، وكذلك معرفة أثر مخاطر السيولة على الربحية في الفترة من (2009 – 2014)، لخمسة مصارف تجارية ليبية وهي: (مصرف الجمهورية، مصرف الوحدة، مصرف الصحارى، مصرف التجارة والتنمية، مصرف شمال إفريقيا). ولتحقيق ذلك ولتغطية كافة جوانب البحث تم الاعتماد على المنهج الوصفي بمدخليه الوثائقي والكمي، وتم صياغة فرضية واحدة، وقد اعتمد البحث على تجميع القوائم المالية وتحليل نسب مخاطر السيولة والربحية وإيجاد الارتباط بينها وقياس الأثر بين مخاطر السيولة والربحية، وقد أظهرت نتائج التحليل إن العلاقة بين مخاطر السيولة والربحية عكسية، وأن مخاطر السيولة لا تؤثر على الربحية. وقد أوصى البحث بمجموعة من التوصيات من أهمها: قيام المصرف المركزي بحثَ المصارف التجارية الليبية على وجود آلية مناسبة لقياس ومتابعة مخاطر السيولة بشكل دوري ومستمر. Abstract The aim of the research is to measure liquidity risks and profitability, and to identify the nature of the relationship between liquidity risk and profitability, as well as to know the impact of liquidity risk on profitability in the period from (2009-2014), for five Libyan commercial banks, namely: (Aljomhoria Bank, Alwahda Bank, Alsahara Bank, Bank of Commerce and Development Altejara wa Altanmia, North African Bank shamal afreqia). To achieve this, and to cover all aspects of the research, the descriptive approach was relied upon with its documentary and quantitative inputs, and one hypothesis was formulated,the research relied on compiling the financial statements, analyzing the ratios of liquidity risk and profitability, finding the link between them, and measuring the effect between liquidity risk and profitability. The results of the analysis showed that the relationship between liquidity risk and profitability is inversely related, and that liquidity risk does not affect profitability. The research recommended a set of recommendations, the most important of which are: The Central Bank urged Libyan commercial banks to have an appropriate mechanism to measure and monitor liquidity risks periodically and continuously.